PARAMETRIC ARCHITECTURE AS A MANIFESTATION OF DIGITAL AESTHETICS: A CASE STUDY OF THE TAICHUNG NATIONAL THEATER - A.W., Lie,; J.X., Zhang, (Soegijapranata Catholic University, 2025)
The advancement of digital technology has transformed the paradigm of contemporary architectural design, including through the implementation of parametric architecture, which enables the creation of non-conventional forms and complex digital aesthetics. This study examines the Taichung National Theater in Taiwan as a concrete representation of parametric architecture in a public building. The main issues explored include how parametric design influences form, function, and spatial experience, as well as its reception within the local social and cultural context. This research employs a qualitative case study method, with data collected through interviews, direct observation, and visual documentation. The findings reveal that the parametric approach enables organic and efficient design, while also offering dynamic and interactive spatial experiences. The integration of digital technologies such as BIM and generative design plays a crucial role in realizing complex and unique architectural forms. In conclusion, parametric architecture is not merely a visual approach, but also a design strategy that impacts spatial perception and local architectural identity. This study offers both theoretical and practical contributions to understanding the potential of digital architecture as a medium for innovation and a shaper of future public space character.